2022
DOI: 10.1590/s0102-0536-20220406
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and substrates for seedlings cultivation of Melocactus zehntneri

Abstract: The populations of Melocactus zehntneri 'chapéu-de-frade' have shown an alarming decline due to the constant withdrawal of individuals from their natural areas. The low percentage of germination of M. zehntneri seeds, added to the slow growth, requires a system for commercial propagation of this species. This study aimed to test the influence of water, hydrochloric acid or acetic acid pre-treatments on seed germination and the influence of different substrates on the initial development of M. zehntneri seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…However, this is not the only reason, since the soil microbiological status may affect it as well, such as the case of fusarium attack of seeds. Our results agreed with several studies which report that the composition and granulometry of the substrate are detrimental to the germination rate difference [42,43]. According to Willmensen [44], it is advisable to use a loose substrate, such as in S1 and S6, rather than a compressed substrate, as in the case of S2, for improving the germination rate.…”
Section: Germinationsupporting
confidence: 91%
“…However, this is not the only reason, since the soil microbiological status may affect it as well, such as the case of fusarium attack of seeds. Our results agreed with several studies which report that the composition and granulometry of the substrate are detrimental to the germination rate difference [42,43]. According to Willmensen [44], it is advisable to use a loose substrate, such as in S1 and S6, rather than a compressed substrate, as in the case of S2, for improving the germination rate.…”
Section: Germinationsupporting
confidence: 91%
“…Successful in vitro germination was reported for M. glaucescens (68.1%), M. sergipensis (64%), M. zehntneri (58.7%), and M. violaceus (59.3%) [ 14 ]. Additionally, previous results obtained by our group have demonstrated similar percentages of seeds germinated in Petri dishes (50–55% on average) for M. zehntneri [ 15 ]. Thus, the results obtained with different species of Melocactus showed that a substantial part of the seeds (40–80%) continues with some unknown type of dormancy, with no germination.…”
Section: Introductionsupporting
confidence: 67%
“…Interestingly, even after a short period of darkness (10 days), seeds did not germinate even after up to 12 months under the same light conditions that promote germination, with the probable acquisition of secondary dormancy due to the absence of light. Under light conditions, the percentage of germinated seeds of M. zehntneri was, on average, 40–60% [ 15 ], showing their photoblastic positive response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation